Analisis Survival Model Regresi Parametrik Lama Studi Mahasiswa - Chandra, Novita Eka; Rohmaniah, Siti Alfiatur (Jurnal Matematika; Vol 9 No 1 (2019), 2019)
Timely graduation of students can be used as an indicator to show the quality of a university. Students are said to graduate on time if they have a short study period of 4 years. The duration of the study of students varies because it is influenced by several factors. The purpose of this study is to determine the factors that have a significant effect on the duration of student studies. The factors studied included gender, GPA, school origin, joining the organization and working in college. The method used in this study is survival analysis. Survival analysis in this study used Log-normal and Weibull, parametric regression models. From the two models, it was found that the GPA and organizational factors significantly influence the duration of student studies. Next, to determine the best model is determined based on the minimum AIC value. Based on the comparison of the two models, the parametric Weibull model has a minimum AIC value, so this model is the best model. Based on HR values ??obtained by students who have a higher GPA and are more active in graduating faster or can be said to have fewer studies. Keywords : survival, regression, parametric, time of study.